Stephen Tyree: capstone - Tyree, Stephen, artist (Colorado State University. Libraries, 2018)
The artist's statement: Stephen Tyree is a graphic designer who strives to create original imagery while heavily focusing on illustration in his artwork. His creations often have had two facets; either his artwork is nostalgic and fun loving, or it is edgy and thought provoking. Tyree enjoys grabbing the attention of viewers by using dynamic compositions and vibrant color schemes, but upon closer examination the work allows the viewer to explore details. As there is desire for escapism but is not ignorant or oblivious to the harsh reality of life and culture. Stephen Tyree primarily uses Adobe Creative suite to design and compose artworks. He is fluent with printmaking, drawing, painting and sculpture for creating art. This does not mean he is limited to these artistic mediums; Stephen Tyree finds great value in artistic exploration to make breakthroughs and discoveries. Tyree currently lives and works out of Fort Collins, Colorado.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design